Newer Effective Treatment for Adult Acute Asthmatics with a Multi-Dose Regimen of Ipratropium Bromide Plus Salbutamol Using Metered Dose Inhalers with a Spacer Device in Emergency Department - Rashid, Md. Mamunur; Khair, Mohammad Murtaza; Hossain, Md. Ali; Hassan, Md. Rashidul (Journal of Bangladesh College of Physicians and Surgeons, 2013)
J Bangladesh Coll Phys Surg 2012; 30: 195-200 DOI: http://dx.doi.org/10.3329/jbcps.v30i4.14761